Disturbed nitric oxide signalling gives rise to congenital bicuspid aortic valve and aortopathy - Joshua C. Peterson; Lambertus J. Wisse; Valerie Wirokromo; Tessa van Herwaarden; Anke M. Smits; Adriana C. Gittenberger-de Groot; Marie-José T. H. Goumans; J. Conny VanMunsteren; Monique R. M. Jongbloed; Marco C. DeRuiter (Disease Models & Mechanisms, 2020)
Patients with a congenital bicuspid aortic valve (BAV), a valve with two instead of three aortic leaflets, have an increased risk of developing thoracic aneurysms and aortic dissection. The mechanisms underlying BAV-associated aortopathy are poorly understood. This study examined BAV-associated aortopathy in Nos3−/− mice, a model with congenital BAV formation. A combination of histological examination and in vivo ultrasound imaging was used to investigate aortic dilation and dissections in Nos3−/− mice. Moreover, cell lineage analysis and single-cell RNA sequencing were used to observe the molecular anomalies within vascular smooth muscle cells (VSMCs) of Nos3−/− mice. Spontaneous aortic dissections were found in ascending aortas located at the sinotubular junction in ∼13% of Nos3−/− mice. Moreover, Nos3−/− mice were prone to developing aortic dilations in the proximal and distal ascending aorta during early adulthood. Lower volumes of elastic fibres were found within vessel walls of the ascending aortas of Nos3−/− mice, as well as incomplete coverage of the aortic inner media by neural crest cell (NCC)-derived VSMCs. VSMCs of Nos3−/− mice showed downregulation of 15 genes, of which seven were associated with aortic aneurysms and dissections in the human population. Elastin mRNA was most markedly downregulated, followed by fibulin-5 expression, both primary components of elastic fibres. This study demonstrates that, in addition to congenital BAV formation, disrupted endothelial-mediated nitric oxide (NO) signalling in Nos3−/− mice also causes aortic dilation and dissection, as a consequence of inhibited elastic fibre formation in VSMCs within the ascending aorta.